Forkhead Box Transcription Factor (FOXO3a) mediates the cytotoxic effect of vernodalin in vitro and inhibits the breast tumor growth in vivo - Sadagopan, S.K.A.; Mohebali, N.; Looi, C.Y.; Hasanpourghadi, M.; Pandurangan, A.K.; Arya, A.; Karimian, H.; Mustafa, Mohd Rais (BioMed Central, 2015)
Background: Natural compounds have been demonstrated to lower breast cancer risk and sensitize tumor cells to anticancer therapies. Recently, we demonstrated that vernodalin (the active constituent of the medicinal herb Centratherum anthelminticum seeds) induces apoptosis in breast cancer cell-lines. The aim of this work was to gain an insight into the underlying anticancer mechanism of vernodalin using in vitro and in vivo model. Methods: Vernodalin was isolated through the bioassay guided fractionation from the seeds. The protein expression of p-Akt, PI3K, FOXO3a, Bim, p27kip1, cyclinD1, and cyclinE was examined by the Western blot analysis. Immunoprecipitation assays were performed to analyse Akt kinase activity. Small interfering RNA (siRNA) was used to study the role of FOXO3a upregulation and their targets during vernodalin treatment. Immunofluorescence, subcellular localisation of FOXO3a by Western blot was performed to analyse FOXO3a localisation in nucleus of breast cancer cells. Immunohistochemical analysis of PCNA, Ki67, p27kip1, FOXO3a and p-FOXO3a in the LA7-induced mammary gland tumor model was performed. Results: Our results showed that vernodalin regulates cancer cell apoptosis through activation of FOXO transcription factors and its downstream targets (Bim, p27Kip1, p21Waf1/cip1, cyclin D1, cyclin E) as examined by Western blots. Furthermore, we showed that FOXO3a/PI3K-Akt played a significant role in vernodalin induced apoptosis in breast cancer cells. Immunoprecipitation assays showed Akt kinase activity was downregulated. Immunofluorescence, subcellular fractionation and Western blot showed FOXO3a accumulation in the nucleus of breast cancer cells after vernodalin treatment. Silencing of FOXO3a protected breast cancer cells against vernodalin induced apoptosis. The anti-tumor action of vernodalin was further confirmed by examining cell proliferative markers, PCNA and Ki67 in the LA7-induced mammary gland tumor model. We also corroborated our findings in vivo by showing upregulation of p27Kip1, FOXO3a and decrease in the p-FOXO3a level in vernodalin-treated breast tumor tissue. Conclusions: Our results suggest that PI3K-Akt/FOXOa pathway is a critical mediator of vernodalin-induced cytotoxicity and this compound could be further developed as a potential chemopreventive or chemotherapeutic agent for breast cancer therapy.